Recent advances in mathematics for engineering - Ram, Mangey (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"In recent years, mathematics has had an amazing growth in engineering sciences. Mathematics forms the common foundation of all engineering disciplines. This new book provides a comprehensive range of mathematics applied in various fields of engineering for different tasks such as civil engineering, structural engineering, computer science, electrical engineering, among others. It offers articles that develop the applications of mathematics in engineering sciences, conveys the innovative research ideas, offers real-world utility of mathematics, and has a significance in the life of academics, practitioners, researchers, and industry leaders"--
OCLC-licensed vendor bibliographic record.
Keywords: Engineering mathematics; TECHNOLOGY / Operations Research; MATHEMATICS / Applied; TECHNOLOGY / Quality Control